Time–frequency and functional connectivity analysis in drug‐naive adolescents with depression based on electroencephalography using a visual cognitive task: A comparative study. - Zhang, Yaru; Yang, Tingyu; Jin, Xingyue; Huang, Jinqiao; Li, Zexuan; Huang, Chunxiang; Luo, Xuerong; He, Yuqiong; Cui, Xilong (Journal of Child Psychology & Psychiatry, 2025)
Background: Previous research studies have demonstrated cognitive deficits in adolescents with depression; however, the neuroelectrophysiological mechanisms underlying these deficits remain poorly understood. Utilizing electroencephalography (EEG) data collected during cognitive tasks, this study applies time–frequency analysis and functional connectivity (FC) techniques to explore the neuroelectrophysiological alterations associated with cognitive deficits in adolescents with depression. Methods: A total of 173 adolescents with depression and 126 healthy controls (HC) participated in the study, undergoing EEG while performing a visual oddball task. Delta, theta, and alpha power spectra, along with FC, were calculated and analyzed. Results: Adolescents with depression exhibited significantly reduced delta, theta, and alpha power at the Fz, Cz, C5, C6, Pz, P5, and P6 electrodes compared to the HC group. Notably, theta power at the F5 electrode and alpha power at the F5 and F6 electrodes were significantly lower in the depression group than in the HC group. Additionally, cortical FC in the frontal and central regions was markedly decreased in adolescents with depression compared to HC. Conclusions: During cognitive tasks, adolescents with depression display distinct abnormalities in both high‐ and low‐frequency brain oscillations, as well as reduced functional connectivity in the frontal, central, and parietal regions compared to HC. These findings offer valuable neuroelectrophysiological insights into the cognitive deficits associated with adolescent depression.